Optical Coherence Tomography Angiography Flow Signal in Non-Treatment-Naïve Patients with Neovascular Age-Related Macular Degeneration Treated with Faricimab - Max Brinkmann; Tom Müller; Marco Köster; Jakob Schweighofer; Mathis Danckwardt; Giuseppe Giannaccare; Paola Marolo; Enrico Borrelli; Michele Reibaldi; Yosuf El-Shabrawi; Mario Damiano Toro (Medicina)
Background and Objectives: Age-related macular degeneration (AMD) remains a leading cause of legal blindness. Anti-Vascular Endothelial Growth Factor (VEGF) agents are the first-line treatment for neovascular AMD (nAMD). The choroid plays a key role in AMD and is affected by the anti-VEGF treatment. Faricimab, a bispecific antibody additionally targeting angiopoietin 2 (Ang2), was recently approved for nAMD treatment. This study investigates the effect of Faricimab on choroidal flow signal. Materials and Methods: Optical coherence tomography angiography images of 29 nAMD eyes were examined retrospectively. Patients had received treatment with other anti-VEGF agents before Faricimab application. The flow signal in the choroid was measured before, after one and after a series of ≥2 Faricimab injections. Results: The flow signal decreased significantly (p = 0.026) at the choriocapillaris (CC) level after ≥2 injections. The flow signal did not show a significant change in Haller’s layer but increased slightly in Sattler’s layer (p = 0.034). Conclusions: In conclusion, our results show that the flow signal, especially at the CC level, changed during treatment. Despite the known influence of anti-VEGF treatment on the choroid, auxiliary inhibition of Ang2 might enhance this effect. Due to the retrospective nature, moderate sample size and non-treatment, naïve patients, care must be taken while interpreting our observations. Prospective studies with larger sample sizes and treatment-naïve patients will be needed.